OPTIMIZATION OF FISHING SHIP IN MANGGARAI BARAT REGENCY NUSA TENGGARA TIMUR - Edizul Adiwijaya Sadir; Rasdam Rasdam; Fajar Hermawan; Franki Darondo (Politeknik Kelautan dan Perikanan Dumai, 2023)
To realize efficient, sustainable and sustainable use of capture fisheries, it is necessary to regulate the optimum number of fishing facilities or vessels. The purpose of this study is to calculate the optimum allocation of selected fishing vessels. Optimum allocation of fishing vessels of choice or priority to types of superior fish resources based on the maximum allowable potential. The analytical method used to calculate the optimization of fishing vessels using Linear Goal Programming (LGP) analysis. Linear Goal Programming (LGP) analysis is used to analyze the dynamics of capture fisheries management which is focused on the optimum allocation of the needs of existing fishing vessels. Linear Goal Programming (LGP) analysis is used to analyze the dynamics of capture fisheries management which is focused on the optimum allocation of the needs of existing fishing vessels. The optimal allocation of fishing vessels to catch Grouper, Snapper and Mackerel is fishing gear (X4) with a size of <5 GT, an allocation of 1,201 vessels per year. To catch the kite and cob commodities, three types of fishing gear were allocated, namely ring purseseine (X1) as many as 10 vessels with a size of 10-15 GT, an allocation of 10 vessels per year, a lift net (X2) with a size <5 GT, an allocation of 150 vessels per year. and gill nets (X3) with a size of <5 GT with an allocation of 100 vessels per year.